2006
DOI: 10.1016/j.ymthe.2006.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell-Based Tumor Vaccines and Antigen Presentation Attenuators

Abstract: Dendritic cell (DC)-based tumor vaccines are being extensively tested to treat cancer patients. Although the results of most DC-based clinical trials have been disappointing, recent advances in the basic molecular understanding of positive and negative regulation of antigen presentation and immune responses can form a basis to enhance the efficacy of DC-based vaccines. Here we describe the new understanding of the importance of Toll-like receptor, tumor necrosis factor receptor, and cytokine receptor signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 105 publications
0
15
0
Order By: Relevance
“…Recent studies have shown that strong innate immunity is required to develop a potent adaptive immune response (39 -42). In addition, increasing evidence suggests that the innate immune system is complex, and maximum activation is a result of interactions between multiple cell types (29,39,40,(42)(43)(44). Current cancer vaccines have focused on Ag-loaded mDC, but we show that optimal immunization may occur with the appropriate interplay between multiple cell types.…”
Section: Discussionmentioning
confidence: 78%
“…Recent studies have shown that strong innate immunity is required to develop a potent adaptive immune response (39 -42). In addition, increasing evidence suggests that the innate immune system is complex, and maximum activation is a result of interactions between multiple cell types (29,39,40,(42)(43)(44). Current cancer vaccines have focused on Ag-loaded mDC, but we show that optimal immunization may occur with the appropriate interplay between multiple cell types.…”
Section: Discussionmentioning
confidence: 78%
“…It has been generally acknowledged that there are many cytokines in the microenvironment of tumor tissues, such as TGF-b, VEGF, IL-10, gangliosides [Shurin, 2001;Peguet-Navarre, 2003] and PGE 2 [Kalinski et al, 1997], etc., that solely or cooperatively suppress the antigen presenting function of DCs, to result in immunotolerence of the tumor cells [Gabrilovich et al, 1997;Allavena et al, 1998;D'Orazio and Niederkorn, 1998;Almand et al, 2000]. The functional defects in DCs and their mechanisms caused by cancer are widely reviewed [Gabrilovich, 2004;Pinzon-Charry et al, 2005;Evel-Kabler and Chen, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…CCL21 can promote the colocalization of naı¨ve T cells, nonpolarized memory T cells and DCs within the lymphoid node and Peyer's patch, leading to antigen presentation and T cell maturation indirectly (Campbell et al, 2001;Baekkevold et al, 2001). DCs, a sort of professional antigen-presenting cell (APC), are highly specialized in antigen uptake and presentation to T cells (Evel-Kabler and Chen, 2006). After the capture of the foreign antigen, DCs process from immature to mature state, which is demonstrated by the up-regulation of the transportation of antigen peptides and expression of co-stimulatory molecules and others, as well as release of cytokines (Tada et al, 2003;Shin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%